Application of correlation pattern recognition technique for neutron– gamma discrimination in the EJ-301 liquid scintillation detector - Phan, Van Chuan; Truong, Van Minh; Bui , Thanh Trung; Nguyen , Thi Phuc; Tran Ngọc, Dieu Quynh (Nuclear Science and Technology, 2018)
The ability to distinguish between neutrons and gamma-rays is important in the fast - neutron detection, especially when using the scintillation detector. A dual correlation pattern recognition (DCPR) method that was based on the correlation pattern recognition technique has been developed for classification of neutron/gamma events from a scintillation detector. In this study, an EJ-301 liquid scintillation (EJ301) detector was used to detect neutrons and gamma-rays from the 60Co and 252Cf sources; the EJ301 detector's pulses were digitized by a digital oscilloscope and its pulse-shape discriminant (PSD) parameters were calculated by the correlation pattern recognition (CPR) method with the reference neutron and gamma-ray pulses. The digital charge integration (DCI) method was also used as a reference-method for comparison with DCPR method. The figure-ofmerit (FOM) values which were calculated in the 50 ÷ 1100 keV electron equivalent (keVee) region showed that the DCPR method outperformed the DCI method. The FOMs of 50, 420 and 1000 keVee thresholds of DCPR method are 0.82 , 2.2 and 1.62, which are 1.55, 1.77, and 1.1 times greater than the DCI method, respectively.